Physician Distribution Outweighs Climate Variability in Shaping Pulmonary Tuberculosis Patterns - Laura Dwi Pratiwi; Yoerdy Agusmal Saputra; Dwi Septiawati; Yustini Ardillah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Pulmonary tuberculosis remains a public health burden in endemic urban areas, exacerbated by heterogeneous climate variability and limited health service capacity. This study aimed to describe the temporal patterns of climate variability and the spatial patterns of physician distribution and their relationship to tuberculosis cases in Palembang. Using a spatial-temporal ecological design, we analyzed monthly time series of tuberculosis cases and summarized monthly climate data from the Meteorology, Climatology, and Geophysics Agency of Indonesia, then mapped the cases and availability of general practitioners and pulmonologits in 18 subdistricts using geographic information system to explore distribution patterns and potential detection bias. The results showed that at the aggregate level, there was no consistent linear relationship between climate fluctuations and variations in pulmonary tuberculosis cases; instead, spatial mapping revealed heterogeneity in cases correlated with medical personnel availability, areas with higher health worker density reported higher cases (indicating increased detection), while resource-limited areas risked underreporting and delayed diagnosis. These findings underscore the need for equitable primary care services, strengthened active case finding, and integration of service indicators into spatial surveillance to improve programmatic detection and response. Keywords: climate variability; physician availability; pulmonary tuberculosis; spatial-temporal patterns